PENGGUNAAN ANTIMIKROBA DARI ISOLAT Lactobacillus TERSELEKSI SEBAGAI BAHAN PENGAWET ALAMI UNTUK MENGHAMBAT PERTUMBUHAN VIBRIO SP. DAN Staphylococcus aureus PADA FILLET IKAN KAKAP - Titin Yulinery; I.Y. Petria; Novik Nurhidayat (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
The fillet of kakap fish is easy to spoil, because of bacteria deterioration. Antimicrobes produced by Lactobacillus is one of save alternatives. The aim of this research was to know the potency of antimicrobes produced by the selected Lactobacillus to inhibit the growth of pathogenic bacteria that contaminated the kakap fillet such as Vibrio sp. and S. aureus. Selected Lactobacillus had been done by the variation of temperature treatments. Diffusion method was used to mesure the wide of clear zone made by Vibrio sp.and S. aureus. In application, antimicrobe solution of selected microbes was used for soaking the kakap fillet, then the bacteria grown were counted on the beginning and the seventh day. The result shown that the wide of the inhibition area on Vibrio sp. was wider compare to the inhibition area made by S. aureus of kakap fillet. At treatment of temperature, antimicrobe solution remain to be active, only its resistivity depend on stability of antimicrobe yielded by selected Lactobacillus. For application used the antimicrobe produced by Lactobacillus (Mar 8) could inhibit the growth of Vibrio sp. and S. aureus on the 0 day and the seventh day, so that compound of antimicrobe can be used as natural preservative at fish product.